Principles of corporate finance - Brealey, Richard A.; Myers, Stewart C.; Allen, Franklin, 1956- (New York : McGraw-Hill Irwin, 2011)
This new international edition provides increased coverage of the procedures for estimating the cost of capital, expanded coverage of risk management techniques and the use and misuse of derivatives, and additional coverage of agency problems.
Previous ed.: 2008.
Includes bibliographical references and index.
Specialized.
Keywords: Corporations -- Finance